Konsep Tujuan Pendidikan Islam Menurut Muhammad Quraish Shihab Dalam Qs Al- Baqarah Ayat 30, Qs Hud Ayat 61, Qs Adz- Dzariyat Ayat 56 - Sarah Dalila Fitri; Rodia Rotani Rianda; Bella Anggraini; Lara Dwi Alma; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Education is an activity that proceeds through stages and levels. After the effort or activity is completed, it is hoped that the goal will be achieved. Because it is gradual and multilevel, the goal of education is not a fixed and static object, but it is the whole of a person's personality, relating to all aspects of his life. The aim of this research is to reveal the concept of the goals of Islamic education in the view of Qurais Sihab. The method used in this research is a qualitative method with a library research approach by using books, magazines and articles related to this research theme as the main data source. The results of this research show that; The concept of the aim of Islamic education contained in QS Al-Baqarah verse 30 is to develop humans individually and in groups so that they are able to carry out their functions as His servants and caliphs, in order to build this world in accordance with the concept set by Allah SWT, while the concept of the aim of Islamic education is contained in QS Hud verse 61 are, being able to create a pious servant, showing the breadth of Allah's knowledge, the formation of noble morals in students which is found in the application of moral education itself, producing knowledgeable students, producing capable students, and The concept of the aim of Islamic education in QS Ad-Dzariyat verse 56 is to form obedient and obedient humans, especially to the Creator. Because the characteristic of an educated person is obedience and obedience to applicable norms and rules.